2012
DOI: 10.1111/j.1365-2834.2012.01473.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical nurses' research capacity in a Norwegian university hospital: part 2

Abstract: The findings from this survey should be useful for professional development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(53 citation statements)
references
References 32 publications
1
51
0
1
Order By: Relevance
“…Professors (chairs) who are leaders in their fields and clinical nurses with a MSc or a PhD degree could serve as inspirational agents of change (Girot , Akerjordet et al . , Jamerson & Vermeersch ). Both are important as role models and research supervisors, as they contribute research capacity building that enables transformative learning (Henderson et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Professors (chairs) who are leaders in their fields and clinical nurses with a MSc or a PhD degree could serve as inspirational agents of change (Girot , Akerjordet et al . , Jamerson & Vermeersch ). Both are important as role models and research supervisors, as they contribute research capacity building that enables transformative learning (Henderson et al .…”
Section: Discussionmentioning
confidence: 97%
“…The seven stages included were: exploratory, literature review, design, preparation for action, action, data analysis and writing‐up phase (Akerjordet et al . ). Space for additional comments was provided at the end of the questionnaire.…”
Section: Methodsmentioning
confidence: 97%
“…Seven studies reported using a theoretical or model framework for guidance. Five studies contained demographic characteristics [33] [34] [36]- [38]. Two studies had a sample drawn from more than one site [32] [36].…”
Section: Step III Reflection On Quality Assessment and Thematic Analysismentioning
confidence: 99%
“…They are responsible for contributing to the strategic goals of their organisation which often include research objectives (Akerjordet et al . ,b, Timmins et al . ).…”
Section: Introductionmentioning
confidence: 99%